An Ethnographic and Collaborative Model of Inquiry: Activity Centre Project in India - Tiwari, Reena; Pandya, Y. (Springer, 2014)
This chapter proposes an ethnographic and collaborative model of inquiry for executing community scale architectural projects that facilitate capacity building opportunities for all stakeholders involved in the process. Taking on the role of an ethnographer, the designer/architect/researcher is able to locate her- or himself within the time and space of the community. In the process he/she is able to form an insider’s perspective on issues and challenges. Working collaboratively, the intention is to create a horizontal power relation between different stakeholders. The model is described in general terms, then illustrated by a case-study—an Activity Centre project for an Indian slum settlement—then discussed in terms of its capacity building outcomes.The Activity Centre project was initiated by a non-government organization, and involved the local architect, the academic researcher and architecture students, residents of a slum settlement, and skilled labour. Although each stakeholder entered into the project with different objectives, the project outcomes were able to provide benefit to all in a tangible or intangible manner. The chapter reflects on the methods employed in the project and the role of stakeholders at each stage of the process. The importance of the local context is underscored—local people, local resources, local tools and techniques—during the design and construction process, to achieve an outcome that is innovative and engenders reciprocity and learning amongst the stakeholders.